Urgensi Manajemen Peserta Didik dalam Lembaga Pendidikan - Nurul Fika; Ahmad Qurtubi; Machdum Bachtiar (Journal on Education, 2024)
Students are school inputs that affect the quality and achievement of educational goals. Differences in talent, motivation, and characteristics of students, as well as a less than optimal school zoning system can cause the quality of graduates to be less than optimal, currently schools focus more on increasing the quantity than the quality of students, the availability of facilities, inadequate infrastructure, the number of educators and education staff that is not optimal are some of the problems related to students. These problems have an impact on the quality of graduates and the achievement of educational goals in schools. The focus of the problem in this study is the lack of optimal management of students both in terms of planning, coaching, evaluating and transferring students. The purpose of writing this article is to describe and analyze the management of students in educational institutions both in terms of planning, coaching, evaluation and mutation. The writing of this article uses qualitative research methods with a library research approach. The results of this study explain that student management is an activity carried out by the school and related to students. Activities in student management include planning for students (needs analysis, recruitment, selection, orientation), student coaching, student evaluation and student mutation.